(untitled) (Al-Qamar, 2023)
In this article, the compositional reversal of its types (preposition and delay, dhikr and omission, attention, objection/interjection, delay, complement, and completion) and figurative in its sections (similitude, metaphor, metaphor) are studied in simplicity and detail. The researcher not only referred to the types of synthetic and figurative justice, but also mentioned their rhetorical secrets. Note that the article begins with the biography of the poetess Al-Hansa and then deals with the types of lamentations. Because the poem is in the lamentation of Sakhr, the poet’s brother. Then the researcher touched on explaining the difficult words found in the poetry of the poem and wrote the meaning and concept of each line, then he started the analysis to make it easy for the reader, and finally he mentioned the results that the researcher reached during writing the article.